2017
DOI: 10.1038/s41598-017-01632-4
|View full text |Cite
|
Sign up to set email alerts
|

Forbs enhance productivity of unfertilised grass-clover leys and support low-carbon bioenergy

Abstract: Intensively managed grasslands are dominated by highly productive grass-clover mixtures. Increasing crop diversity by inclusion of competitive forbs may enhance biomass production and sustainable biofuel production. Here we examined if one or all of three forbs (chicory, Cichorium intybus L.; caraway, Carum carvi L.; plantain, Plantago lanceolata L.) included in ryegrass-red clover mixtures enhanced above- and below-ground productivity, and assessed their biofuel potentials, based on a three-year experiment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Previous work showed that root biomass of grass- Table 1 Fertiliser history of the Askov LTE. The rate (kg ha −1 yr -1 ) of total nitrogen (N), phosphorus (P) and potassium (K) added in 1 A M (animal manure) and 1 NPK (mineral fertiliser) from 1973 to 2016. legume ley was substantially higher on rows than between rows (Cong et al, 2017) wherefore we quantified root biomass separately for onrow areas and between-row areas. Then whole-plot root biomass was the weighted sum of root biomass in the two areas.…”
Section: Standing Root Biomassmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work showed that root biomass of grass- Table 1 Fertiliser history of the Askov LTE. The rate (kg ha −1 yr -1 ) of total nitrogen (N), phosphorus (P) and potassium (K) added in 1 A M (animal manure) and 1 NPK (mineral fertiliser) from 1973 to 2016. legume ley was substantially higher on rows than between rows (Cong et al, 2017) wherefore we quantified root biomass separately for onrow areas and between-row areas. Then whole-plot root biomass was the weighted sum of root biomass in the two areas.…”
Section: Standing Root Biomassmentioning
confidence: 99%
“…The row distance of grass-legume ley was 12 cm, dividing the plot area into stripes each comprising 6 cm-wide on-row area and 6 cm-wide between-row area. Six random cores were taken in the on-row area and another three in the between-row area to account for the higher variation in the on-row area (Cong et al, 2017). In total, we collected 180 cores (20 plots × 9 cores).…”
Section: Standing Root Biomassmentioning
confidence: 99%
“…Inclusion of plantain significantly enhanced herbage yield of the reference mixture, while the same pattern was also observed for root biomass (see Fig. 4 in Cong et al, 2017). Surprisingly, neither herbage yield nor root biomass significantly correlated with any of soil chemical or microbial variables, except for a positive correlation between herbage yield and k (Table 3).…”
Section: Correlations Between Soil Properties Herbage Yield Root Bimentioning
confidence: 62%
“…The grasslands, established in spring 2013 in a long-term organic dairy crop rotation on loamy sand (Eriksen et al, 2015), were composed of red clover (Trifolium pratense L., variety Rajah), perennial ryegrass (Lolium perenne L., variety Stefani), chicory (Cichorium intybus L., variety Spadona), ribwort plantain (Plantago lanceolata L., wild type) and caraway (Carum carvi L., variety Volhouden) in different seeding mixtures (Table 1) and managed as described in Cong et al (2017). The resultant swards varied in red clover proportion, input of N from N 2 -fixation (246-617 kg N/ha), and N balance (À54 to 137 kg N/ha) depending on species composition in the seed mixtures (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, nonlegume forbs have been included in grassclover mixtures to improve mineral nutrition for grazing animals from the forage (Pirhofer-Walzl et al, 2011), plant diversity and herbage production (Cong et al, 2017). In grasslands, legume biomass is an indicator of N released to the subsequent crop (Vrignon-Brenas et al, 2016); hence, inclusion of nonlegume forbs could affect the residual N fertility due to their replacement of N-rich legumes in the sward.…”
Section: Introductionmentioning
confidence: 99%